(untitled) (Journal of Health, Population and Nutrition, 2010)
A cross-sectional community-based study with analytic component was conducted among Ethiopian women during June-July 2005 to assess the magnitude of anaemia and deficiencies of iron and folic acid and to compare the factors responsible for anaemia among anaemic and non-anaemic cases. In total, 970 women, aged 15-19 years, were selected systematically for haematological and other important parameters. The overall prevalence of anaemia, iron deficiency, iron-deficiency anaemia, deficiency of folic acid, and parasitic infestations was 30.4%, 50.1%, 18.1%, 31.3%, and 13.7% respectively. Women who had more children aged less than five years but above two years, open-field toilet habits, chronic illnesses, and having intestinal parasites were positively associated with anaemia. Women who had no formal education and who did not use contraceptives were negatively associated with anaemia. The major determinants identified for anaemia were chronic illnesses [adjusted odds ratio (AOR)=1.1, 95% confidence interval (CI) 1.15-1.55), deficiency of iron (AOR=0.4, 95% CI 0.35-0.64), and deficiency of folic acid (AOR=0.5, 95% CI 0.50-0.90). The odds for developing anaemia was 1.1 times more likely among women with chronic illnesses, 60% more likely in the iron-deficient and 40% more likely in the folic acid-deficient than their counterparts. One in every three women had anaemia and deficiency of folic acid while one in every two had iron deficiency, suggesting that deficiencies of both folic acid and iron constitute the major micronutrient deficiencies in Ethiopian women. The risk imposed by anaemia to the health of women ranging from impediment of daily activities and poor pregnancy outcome calls for effective public-health measures, such as improved nutrient supplementation, health education, and timely treatment of illnesses. Key words: Anaemia; Anaemia, Iron-deficiency; Community-based studies; Cross-sectional studies; Folic acid; Iron deficiency; Ethiopia DOI: 10.3329/jhpn.v28i4.6042 J HEALTH POPUL NUTR 2010 Aug;28(4):359-368